'Influence of Draft Tube Diameter on Operation Behavior of Air Lift Loop Reactors - Al-Azzi, Ali Abdul-Rahman; S. Al-Kuffe, Laith S. (Al-Khwarizmi Engineering Journal, 2010)
The ratio of draft tube to reactor diameters is of decisive importance for the operation behavior of air lift loop reactors. The influence of draft tube geometry was investigated with respect to oxygen mass transfer and mixing time. The diameter ratio was varied between 0.33 and 0.80. The measurements were performed in two loop reactors with liquid capacities of 11.775 and 26.49 liters using aqueous with solutions of different coalescence behavior. The results show that there is no single diameter ratio which would produce most favorable conditions for the two process parameters. With respect to the more important requirements of aerobic cultures, i.e high oxygen mass transfer and efficient mixing, a diameter ratio between 0.5 and 0.6 is recommended. If high liquid velocities in the draft tube are required a ratio of 0.6 should be used.